Improved Fractional Channel Estimation for MIMO Systems in the Low SNR Regime - Singh, Simranjit; Khanna, Rajesh; Patterh, Manjeet Singh (Elektronika ir Elektrotechnika, 2013)
In this paper, we propose a novel fractional channel estimation technique for block faded MIMO systems. The existing channel estimation techniques perform the estimation in the time domain which is appropriate for acceptable SNR levels. At low SNR levels, noise which is a major source of errors cannot be separated effectively in time domain. However, fractional domain processing of signals has been shown to be effective in minimizing the errors due to noise. The signal which appears scattered in time domain due to noise appears to be compact in the optimum fractional domain where the effects of noise can be minimized. Based on this principle, a novel channel estimation algorithm is proposed for the low SNR applications. It is seen that the proposed technique clearly outperforms the existing channel estimation technique. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.3259